Response of Metastatic Chordoma to the Immune Checkpoint Inhibitor Pembrolizumab: A Case Report - Wu, Xiaoli; Lin, Xiangwu; Chen, Ying; Kong, Wencui; Xu, Jinhe; Yu, Zongyang (Frontiers in Oncology, 2020)
Chordoma is a rare primary bone tumor that exhibits insensitivity to radiotherapy and chemotherapy and has a poor prognosis. Currently, resection is the primary treatment for affected patients, but the subsequent rate of recurrence is high, and both overall survival (OS) and progression-free survival (PFS) are consequentially relatively short. This case report describes a patient who was diagnosed with metastatic chordoma that was found to possess the A1209fs mutation of the PBRM1 gene, which may be associated with beneficial responses to immunotherapies. The patient received pembrolizumab, an immune checkpoint inhibitor (ICI) that targets the PD-1 receptor of lymphocytes, as second-line therapy, which he tolerated well (the most frequent adverse events were abnormal liver function and hyperglycemia, both of which were only grades 1-2), and achieved a PFS duration of 9.3 months. We hope these results will promote further research that will clarify the mechanisms underlying this beneficial response and that will further explore the use of immunotherapies in this population.